Magnesium hydride-based hydrogen storage composite material as well as preparation and application thereof
By using NiS-MoS2 or NiS-rGO composites as modifiers in magnesium hydride-based hydrogen storage materials as modifiers, the problem of unsatisfactory circulation stability of magnesium hydride-based hydrogen storage materials is solved, and more efficient hydrogen storage capacity and circulation are achieved stability.
Patent Information
- Application Number
- CN202310717613.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2024-12-17
AI Technical Summary
The hydrogen storage and discharge cycle stability of existing magnesium hydride-based hydrogen storage materials is not ideal, and it is difficult to achieve long-term stable cycles.
Using nickel monosulfide (NiS) combined with molybdenum sulfide (MoS2) or reduced graphene oxide (rGO) as modifiers, mechanical ball milling with magnesium hydride to prepare composite materials to form NiS-MoS2 or NiS-rGO composites to improve their Hydrogen storage capacity and cycle stability.
It effectively improves the hydrogen storage capacity of magnesium hydride and the circulation stability of hydrogen storage, and improves the long-range circulation performance of the material.
Smart Images

Figure CN119143079A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of clean energy materials, and specifically relates to the field of magnesium hydride-based hydrogen storage materials. Background Art
[0002] Energy is the material basis for the continuous development of society and the cornerstone for human survival and development. However, after the first industrial revolution in the 18th century, the world's consumption of energy, especially fossil energy, continued to rise. These traditional fossil fuels not only have limited reserves, but also cause environmental pollution if burned excessively. Among many renewable energy sources, hydrogen energy is considered to be one of the most promising green energy sources due to its advantages such as abundant reserves, high calorific value, strong renewability and good environmental protection. For the large-scale application of hydrogen energy, hydrogen storage technology is crucial. Solid hydrogen storage materials have become the focus of researchers due to their advantages such as high hydrogen storage density, high safety and easy transportation.
[0003] Among solid-state hydrogen storage materials, magnesium-based hydrogen storage materials (MgH2) have attracted much attention due to their abundant reserves, low prices, and low hydrogen desorption temperatures. For MgH2, researchers focus on improving kinetic performance, and there is little research on the cycle performance of composite hydrogen storage materials, which will affect its industrialization process. Among them, metal sulfides and carbon materials have a certain effect on improving the cycle stability of MgH2. At the same time, the preparation of composite materials by doping catalysts and MgH2 through mechanical ball milling is simple and practical. However, the existing doping ideas mainly consider the capacity problem of MgH2, and have not explored the long-term cycle stability of the material too much. Summary of the invention
[0004] In view of the problem that existing magnesium hydride-based hydrogen storage materials have unsatisfactory hydrogen storage and desorption cycle stability, the first object of the present invention is to provide a magnesium hydride-based hydrogen storage composite material, aiming to improve performance such as cycle stability and capacity.
[0005] The second object of the present invention is to provide a method for preparing the magnesium hydride-based hydrogen storage composite material and its application as a hydrogen storage active material.
[0006] The third object of the present invention is to provide a device comprising the magnesium hydride-based hydrogen storage composite material.
[0007] The prior art provides some solutions for modifying magnesium hydride with nickel disulfide, molybdenum sulfide, etc. Although such methods can improve the hydrogen storage capacity of magnesium hydride to a certain extent, their contribution to cycle stability is limited, and it is difficult to achieve long-term stable cycle. In view of this problem, the present invention provides the following improvement scheme:
[0008] A magnesium hydride-based hydrogen storage composite material, comprising magnesium hydride and a modifier;
[0009] The modifier is at least one of a NiS-MoS2 composite and a NiS-rGO composite.
[0010] The present invention innovatively discovered that the composite of nickel monosulfide (divalent nickel sulfide, NiS) and (MoS2 and / or rGO) can unexpectedly achieve synergy, which can not only improve the hydrogen storage capacity of magnesium hydride, but also unexpectedly effectively improve the cyclic stability of its hydrogen storage and release.
[0011] In the present invention, the composite of the nickel sulfide and (MoS2 and / or rGO) is the key to synergistically solving the problem of its unsatisfactory cycle stability.
[0012] Preferably, the NiS-MoS2 composite is a mixture of NiS and MoS2, preferably a mixture formed by ball milling;
[0013] Preferably, the weight ratio of NiS to MoS2 is 1-4:1-4, more preferably 1:1-2, and even more preferably 1:1.3-1.8. Under the preferred ratio, the hydrogen storage capacity of the material can be further synergistically improved, and the cycle performance can also be improved.
[0014] Preferably, the NiS-rGO composite comprises an rGO substrate and NiS nanoparticles loaded on the surface thereof;
[0015] Preferably, in the NiS-rGO composite, the weight ratio of NiS to rGO is 3.5 to 0.5:1, more preferably 3 to 1:1, and even more preferably 1 to 1.5:1.
[0016] Preferably, the weight ratio of magnesium hydride to modifier is 99-97:1-3. More preferably, the weight percentage of modifier in the magnesium hydride-based hydrogen storage composite material is 1-3%, and more preferably 1.5-2.5%.
[0017] The present invention also provides a method for preparing the magnesium hydride-based hydrogen storage composite material, wherein NiS and MoS2 are prepared separately, and then the two are compounded to obtain the NiS-MoS2 composite; or a NiS-rGO composite is prepared by a one-pot hydrothermal method; and then a modifier containing the NiS-MoS2 composite and / or the NiS-rGO composite is compounded with magnesium hydride to obtain the magnesium hydride-based hydrogen storage composite material;
[0018] Alternatively, NiS, MoS2 and magnesium hydride are directly compounded to obtain the magnesium hydride-based hydrogen storage composite material.
[0019] The present invention innovatively finds that by preparing NiS and MoS2 separately and then compounding them, the hydrogen storage capacity and the cyclic stability of hydrogen storage and release of magnesium hydride can be unexpectedly synergistically improved.
[0020] In the present invention, the NiS, MoS2 and NiS-rGO composites can be prepared based on known methods.
[0021] In the present invention, a nickel source and a sulfur source can be used to carry out a hydrothermal reaction A to prepare NiS;
[0022] Preferably, the nickel source is a water-soluble salt of Ni ions, preferably at least one of nickel acetate, nickel nitrate, nickel sulfate, and nickel citrate;
[0023] The sulfur source elemental sulfur and its compounds are preferably at least one of thiourea, sulfur, thioacetamide, sodium sulfide, and 1-butyl-3-methylimidazole thiocyanate;
[0024] Preferably, in the hydrothermal reaction A, the molar ratio of Ni / S in the nickel source and the sulfur source is 1:(2-5), and considering the processing cost, it can be further 1:2.5-3.5;
[0025] The temperature of the hydrothermal reaction A is 200-240° C.; the time is 18-30 h, and can further be 20-26 h.
[0026] In the present invention, a molybdenum source and a sulfur source can also be used to carry out a hydrothermal reaction B to prepare MoS2.
[0027] Preferably, the molybdenum source is a water-soluble molybdate, preferably at least one of sodium molybdate, ammonium molybdate, molybdenum oxide, and molybdenum;
[0028] Preferably, in the hydrothermal reaction B, the molar ratio of Mo / S in the molybdenum source and the sulfur source is 1:(2-5), and considering the processing cost, it can be further 1:(3-5);
[0029] Preferably, the temperature of the hydrothermal reaction B is 200 to 240° C.; the time is 18 to 30 hours, and further can be 20 to 26 hours;
[0030] Preferably, NiS and MoS2 are compounded based on ball milling, wherein the parameters of ball milling are: the ball-to-material ratio in the ball-to-material stage is (30-40):1, the ball milling speed is 300-500 rpm / min, the ball milling hydrogen pressure is 5-15 bar, and the ball milling time is 3-6 h.
[0031] In the present invention, a raw material solution containing a nickel source, a sulfur source, and rGO is subjected to a hydrothermal reaction C to obtain the NiS-rGO composite. The temperature of the hydrothermal reaction C is 100 to 200° C. (preferably 150 to 190° C.); the time is 18 to 30 hours (preferably 20 to 26 hours). The molar ratio of Ni / S of the nickel source and the sulfur source is 1:2 to 4.
[0032] In the present invention, magnesium hydride and the modifier are compounded based on ball milling, wherein the ball milling parameters are: the ball-to-material ratio in the ball-to-material stage is (30-40):1, the ball milling speed is 300-500 rpm / min, the ball milling hydrogen pressure is 5-15 bar, and the ball milling time is 3-6 hours.
[0033] The present invention also provides an application of the magnesium hydride-based hydrogen storage composite material as a hydrogen storage active material.
[0034] In the present invention, the magnesium hydride-based hydrogen storage composite material of the present invention can be used as an active material to prepare a hydrogen storage device based on conventional means and methods.
[0035] The present invention also provides a hydrogen storage device, which comprises the magnesium hydride-based hydrogen storage composite material.
[0036] The hydrogen storage device of the present invention, except for the magnesium hydride-based hydrogen storage composite material of the present invention, other components and materials may be known.
[0037] Beneficial Effects
[0038] The present invention innovatively finds that the composite of nickel sulfide and (MoS2 and / or rGO) can unexpectedly achieve synergy, which can not only improve the hydrogen storage capacity of magnesium hydride, but also unexpectedly and effectively improve the cyclic stability of its hydrogen storage and release.
[0039] The present invention unexpectedly discovered that preparing NiS and MoS2 separately and then compounding them with magnesium hydride can unexpectedly further improve the synergy between the two, which helps to further improve the hydrogen storage and release cycle stability of magnesium hydride.
[0040] The modifier of the present invention can synergistically improve the cycle stability of magnesium hydride based on the composite components.
[0041] Description of the drawings (drawings that document the material's physical properties, structural characteristics, performance advantages, and authenticity)
[0042] Figure 1 These are the XRD and SEM images of NiS and MoS2 prepared in step 1 and step 2 of Example 1, wherein parts (ac) are the XRD and SEM images of NiS, and parts (df) are the XRD and SEM images of MoS2.
[0043] Figure 2 50 cycle capacity diagram of the MgH2 and NiS-MoS2 composite material prepared in step 3 of Example 1 at 300°C;
[0044] Figure 3 50 cycle capacity diagram of the MgH2 and NiS composite material prepared in Comparative Example 1 at 300°C;
[0045] Figure 4 50 cycle capacity diagrams of MgH2 prepared in Comparative Example 3 and NiS / MoS2 composite material prepared by one-pot method at 300°C;
[0046] Figure 5 The XRD patterns and SEM images of the NiS-rGO modifiers prepared in Examples 3 and 4. Part (b) is the SEM image of the modifier prepared in Example 3, and part (c) is the SEM image of the modifier prepared in Example 4;
[0047] Figure 6 The 50 cycle capacity diagram of the composite material of MgH2 prepared in Example 3 and only 30 mg rGONiS-rGO added during catalyst preparation at 300°C;
[0048] Figure 7 This is a graph of the 50 cycle capacity of the MgH2 prepared in Example 4 and the NiS-rGO composite material to which only 10 mg rGO was added during catalyst preparation at 300°C; DETAILED DESCRIPTION
[0049] The present invention provides two magnesium-based hydrogen storage materials doped with nickel sulfide-based composite catalysts, which are prepared by mechanical ball milling of magnesium hydride and two nickel sulfide-based modifiers; the modifiers are NiS-MoS2 and NiS-rGO, the NiS-MoS2 modifier is prepared by a hydrothermal method by separately preparing NiS and MoS2 and then ball-milling and mixing, and the NiS-rGO is prepared by mixing rGO (reduced graphene oxide) with a nickel source through a hydrothermal method.
[0050] The present invention also provides a typical method for preparing the magnesium-based hydrogen storage material doped with the nickel sulfide-based composite catalyst, comprising the following steps:
[0051] A. Preparation of NiS material;
[0052] B. Preparation of MoS2 material;
[0053] C. Preparation of NiS-rGO composites;
[0054] D. Preparation of MgH2 and NiS-MoS2 composite materials;
[0055] E. Preparation of MgH2 and NiS-rGO composites;
[0056] Wherein, the step of preparing the NiS material comprises:
[0057] a1. Dissolve nickel acetate tetrahydrate and thiourea in 70-140 ml of deionized water at a molar ratio of nickel to sulfur of 1:(2-5), and stir thoroughly with electromagnetic stirring for 1-3 hours until dissolved;
[0058] a2. The solution is transferred to a hydrothermal reactor, wherein the temperature of the hydrothermal reaction B is 200 to 240°C; the time is 18 to 30h;
[0059] a3. The material after the hydrothermal reaction was first washed with deionized water and then centrifuged with ethanol to remove impurities and dried in an oven at 50 to 90 ° C for 12 to 36 h to obtain a NiS material;
[0060] The steps of preparing the MoS2 material include:
[0061] a1. Sodium molybdate dihydrate (chemical formula: Na2MoO4·2H2O) and thiourea are dissolved in 20-40 ml of deionized water at a molar ratio of molybdenum to sulfur of 1:(2-5), and stirred by electromagnetic stirring for 1-3 hours until dissolved;
[0062] a2. The thiourea solution obtained by stirring was added dropwise to the sodium molybdate dihydrate solution, and stirring was continued for 30 to 90 min until a uniform solution was obtained;
[0063] a3. Add concentrated hydrochloric acid through a dropper while stirring, and use a pH meter to measure the pH of the mixed solution of sodium molybdate dihydrate and thiourea in real time, adjust the pH of the solution to a certain value, and transfer the solution to a hydrothermal reactor, wherein the temperature of the hydrothermal reaction B is 200 to 240°C; the time is 18 to 30 hours;
[0064] a4. The material after the hydrothermal reaction was first washed with deionized water and then centrifuged with ethanol to remove impurities, and then dried in an oven at 50 to 90 ° C for 12 to 36 hours to obtain MoS2 material;
[0065] The steps of preparing the NiS-rGO composite material include:
[0066] c1. Dissolve nickel chloride hexahydrate and thiourea in 20-40 ml of deionized water at a molar ratio of nickel to sulfur of 1:(2-4), and stir thoroughly with electromagnetic for 1-3 hours until dissolved;
[0067] c2. Add distilled water to a certain amount of rGO, dilute to 1 mg / ml, and sonicate for 1 h to make it evenly dispersed;
[0068] c3. The rGO solution obtained by ultrasound is added dropwise to the mixed solution of nickel chloride hexahydrate and thiourea (the weight ratio of rGO to the designed and synthesized nickel monosulfide is 1:1-3), and stirring is continued for 30-90 minutes until a uniform solution is obtained;
[0069] c4. The solution is transferred to a hydrothermal reactor, wherein the hydrothermal reaction temperature is 100 to 200 ° C; the time is 18 to 30h;
[0070] c5. The material after the hydrothermal reaction was first washed with deionized water and then centrifuged with ethanol to remove impurities, and then dried in an oven at 50 to 90° C. for 12 to 36 hours to obtain a NiS-rGO composite material;
[0071] The steps of preparing the MgH2 and NiS-MoS2 composite material include:
[0072] The NiS and MoS2 obtained in the above steps A and B are uniformly mixed with the MgH2 material in a certain mass ratio, and mechanically ball-milled with a planetary ball mill under certain conditions to obtain a NiS-MoS2 composite magnesium-based hydrogen storage material. Specifically, the mass ratio of NiS and MoS2 materials is (1-4): (4-1), and the composite catalyst accounts for 1-3wt.% of the total mass of the composite material; the ball-to-material ratio in the ball-milling conditions is (30-40): 1, the ball-milling speed is 300-500rpm / min, the ball-milling hydrogen pressure is 5-15bar, and the ball-milling time is 3-6h.
[0073] The steps of preparing the MgH2 and NiS-rGO composite material include:
[0074] The NiS-rGO prepared in the above step C is uniformly mixed with the MgH2 material at a fixed mass ratio, and mechanically ball-milled with a planetary ball mill under certain conditions to obtain a NiS-rGO composite magnesium-based hydrogen storage material. The NiS-rGO composite catalyst accounts for 1 to 3 wt.% of the total mass of the NiS-rGO-MgH2 material composite material; the ball-to-material ratio in the ball-milling conditions is (30 to 40): 1, the ball-milling speed is 300 to 500 rpm / min, the ball-milling hydrogen pressure is 5 to 15 bar, and the ball-milling time is 3 to 6 hours.
[0075] Example 1 - NiS / MoS2 solution
[0076] Step 1: Preparation of NiS
[0077] Nickel acetate tetrahydrate (the specific amount used in this case is 0.002 mol) and thiourea are dissolved in 80 ml of deionized water in a molar ratio of nickel to sulfur of 1:3, and electromagnetic stirring is fully performed for 1 hour until dissolved; the solution is transferred to a hydrothermal reactor and kept warm at 220°C for 24 hours; the material after the hydrothermal reaction is first washed by deionized water and then by ethanol for centrifugation to remove impurities, and then dried in an oven at 80°C for 12 hours to obtain NiS material.
[0078] Step 2: Preparation of MoS2
[0079] Sodium molybdate dihydrate (the specific amount in this case is 0.005 mol) and thiourea are dissolved in 30 ml of deionized water according to the molar ratio of molybdenum to sulfur of 1:4, and electromagnetic stirring is fully carried out for 1 hour until dissolved; the thiourea solution obtained by stirring is added dropwise to the sodium molybdate dihydrate solution, and stirring is continued for 60 minutes until mixed into a uniform solution; concentrated hydrochloric acid is added through a dropper under stirring, and the pH of the mixed solution of sodium molybdate dihydrate and thiourea is measured in real time using a pH meter, and the pH of the solution is adjusted to 2, and the solution is transferred to a hydrothermal reactor and kept warm at 220°C for 24 hours; the material after the hydrothermal reaction is first washed with deionized water and then with ethanol for centrifugation to remove impurities, and dried in an oven at 60°C for 12 hours to obtain MoS2 material.
[0080] Step 3: Preparation of MgH2 and NiS-MoS2 composites
[0081] The NiS, MoS2 and MgH2 materials obtained in the above steps 1 and 2 are uniformly mixed at a ratio of 0.8:1.2:98, and mechanically ball-milled using a planetary ball mill under certain conditions to obtain a NiS-MoS2 composite magnesium-based hydrogen storage material; the ball-to-material ratio under the ball-milling conditions is 35:1, the ball-milling speed is 400 rpm / min, the ball-milling hydrogen pressure is 10 bar, and the ball-milling time is 5 hours.
[0082] The material phase and morphology are shown in Figure 1 , indicating that the physical phase material required by the present invention is obtained.
[0083] test:
[0084] The sample to be tested was placed in a glove box under argon atmosphere and placed in a reactor connected to the HPSA-auto high pressure adsorption instrument, and then heated up and tested. In the cycle test, the temperature was fixed at 300°C, the hydrogen absorption / desorption time was 1h, and the initial hydrogen pressures of hydrogen absorption and desorption were 0.84MPa and 0.004MPa, respectively.
[0085] The hydrogen storage capacity of the magnesium-based hydrogen storage material doped with NiS / MoS2 can be stabilized at 6.4wt.%, and the initial dehydrogenation temperature is reduced to 256℃.
[0086] The cycle results are shown in Figure 2 , showing that under 50 cycles, a retention rate of up to 97% is still achieved.
[0087] Example 2
[0088] Compared with Example 1, the only difference is that the modifier is only a different ratio of NiS, MoS2 and MgH2 materials, and other operations and parameters are the same as Example 1.
[0089] When the ratio of NiS, MoS2 and MgH2 materials is 0.4:1.6:98, the actual dehydrogenation temperature of the composite magnesium-based hydrogen storage material is 263°C; when the ratio of NiS, MoS2 and MgH2 materials is 1.2:0.8:98, the actual dehydrogenation temperature of the composite magnesium-based hydrogen storage material is 260°C; when the ratio of NiS, MoS2 and MgH2 materials is 1.6:0.4:98, the actual dehydrogenation temperature of the composite magnesium-based hydrogen storage material is 265°C.
[0090] Comparing Examples 1 and 2, it can be seen that when the weight ratio of NiS to MoS2 is 1:1 to 2, better hydrogen production performance can be obtained, and the catalyst with the preferred ratio can show excellent cycle stability.
[0091] Comparative Example 1
[0092] Compared with Example 1, the only difference is that the modifier is only NiS, NiS and MgH2 are uniformly mixed at a ratio of 2:98, and other operations and parameters are the same as Example 1. The cycle test is carried out according to the method of Example 1, and the results are shown in Figure 3 After 50 cycles, the decay rate is reduced to about 80%.
[0093] Comparative Example 2
[0094] Compared with Example 1, the only difference is that in the modifier, NiS2 (nickel disulfide) of equal weight is used to replace the NiS, and other operations such as the ratio of NiS2 / MoS2 and the content in the composite catalyst are the same as in Example 1. The hydrogen storage capacity of the magnesium-based hydrogen storage material doped with MoS2 / NiS2 is only 6wt.%, which is less than that of Example 1, and the cycle test is carried out according to the method of Example 1. After 50 cycles, it decays to 90%, and the cycle stability is also not as good as that of Example 1.
[0095] Comparative Example 3
[0096] Compared with Example 1, the only difference is that NiS / MoS2 of equal weight ratio is prepared in one pot, and the steps are as follows:
[0097] 1. Disperse 1.58 g of 1-butyl-3-methylimidazole thiocyanate (BMIMSCN) evenly in 16 ml of deionized water and stir for 5 minutes to mix thoroughly;
[0098] 2. Add 0.12 g of nickel chloride hexahydrate to the mixed solution of 1-butyl-3-methylimidazole thiocyanate and stir by electromagnetic stirring for 30 min to form a uniform mixed solution;
[0099] 3. Add 0.134 g of ammonium molybdate tetrahydrate to the mixture of 1-butyl-3-methylimidazole thiocyanate and nickel chloride hexahydrate, and stir by electromagnetic stirring for 10 min to form a uniform mixture;
[0100] 4. The solution was transferred to a hydrothermal reactor and kept at 180°C for 24 hours. The substance after the hydrothermal reaction was first washed by centrifugation with deionized water and then with ethanol to remove impurities, and then dried in a vacuum drying oven at 60°C for 12 hours.
[0101] 5. Pass more than 99% argon gas through the dried material, calcine at a heating rate of 5°C / min for 2 hours, and then cool to room temperature to obtain NiS / MoS2 material.
[0102] 6. The NiS / MoS2 and MgH2 materials prepared in the above steps are uniformly mixed in a ratio of 2:98, and mechanically ball-milled using a planetary ball mill under certain conditions to obtain a NiS / MoS2 composite magnesium-based hydrogen storage material; the ball-to-material ratio under the ball-milling conditions is 35:1, the ball-milling speed is 400 rpm / min, the ball-milling hydrogen pressure is 10 bar, and the ball-milling time is 5 h.
[0103] The cycle test was carried out according to the method of Example 1. The results are shown in Figure 4 After 50 cycles, the decay rate reaches 91%.
[0104] Example 3 - NiS / rGO solution
[0105] Step 1: Preparation of NiS / rGO
[0106] Dissolve nickel chloride hexahydrate and thiourea in 30 ml of deionized water according to the molar ratio of nickel to sulfur of 1:3, and stir them by electromagnetic stirring for 1 hour until dissolved; add distilled water to 30 mg of rGO (the designed weight ratio of NiS / rGO is 1:1), dilute to 1 mg / ml, and ultrasonicate for 1 hour to make it evenly dispersed; add the rGO solution obtained by ultrasonication to the mixed solution of nickel chloride hexahydrate and thiourea by dropwise addition, and continue stirring for 1 hour until mixed into a uniform solution; transfer the solution to a hydrothermal reactor and keep it warm at 180°C for 24 hours; the material after the hydrothermal reaction is first washed by deionized water and then by ethanol for centrifugation to remove impurities, and then dried in an oven at 60°C for 12 hours to obtain a NiS-rGO composite material;
[0107] Step 2: Preparation of MgH2 and NiS-rGO composites
[0108] The NiS-rGO prepared in the above step 1 is uniformly mixed with the MgH2 material at a ratio of 2:98, and mechanically ball-milled using a planetary ball mill under certain conditions to obtain a NiS-rGO composite magnesium-based hydrogen storage material; the ball-to-material ratio in the ball-milling conditions is 35:1, the ball-milling speed is 400 rpm / min, the ball-milling hydrogen pressure is 10 bar, and the ball-milling time is 5 h.
[0109] The phase and morphology of the obtained product are shown in Figure 5. Then the cycle test was carried out according to the method of Example 1, and the results are shown in Figure 6 , and remained at 99% after 50 cycles.
[0110] Example 4
[0111] Compared with Example 3, the only difference is that the amount of rGO added in the composite modifier is 10 mg (the designed weight ratio of NiS / rGO is 3:1), and the other operations and parameters are the same as Example 3.
[0112] The cycle test was carried out according to the method of Example 1, and the results are shown in Figure 7 After 50 cycles, the retention rate can still reach 92%.
Claims
1. A magnesium hydride-based hydrogen storage composite material, characterized in that: It comprises magnesium hydride and a modifier; the modifier is at least one of a NiS-MoS2 composite and a NiS-rGO composite.
2. The magnesium hydride-based hydrogen storage composite material according to claim 1, characterized in that: NiS-MoS2 composite A mixture of NiS and MoS2, preferably a mixture formed by ball milling; Preferably, the weight ratio of NiS to MoS2 is 1-4:1-4.
3. The magnesium hydride-based hydrogen storage composite material according to claim 1, characterized in that: The NiS-rGO composite includes an rGO substrate and NiS nanoparticles loaded on its surface; Preferably, in the NiS-rGO composite, the weight ratio of NiS to rGO is 3.5 to 0.5:1, more preferably 3 to 1:
1.
4. The magnesium hydride-based hydrogen storage composite material according to any one of claims 1 to 3, characterized in that: The weight ratio of magnesium hydride to the modifier is 99-97:1-3.
5. A method for preparing the magnesium hydride-based hydrogen storage composite material according to any one of claims 1 to 4, characterized in that: Prepare NiS and MoS2 separately, and then compound the two to obtain the NiS-MoS2 composite; or prepare the NiS-rGO composite by a one-pot hydrothermal method; and then compound the modifier containing the NiS-MoS2 composite and / or the NiS-rGO composite with magnesium hydride to obtain the magnesium hydride-based hydrogen storage composite material; Alternatively, NiS, MoS2 and magnesium hydride are directly compounded to obtain the magnesium hydride-based hydrogen storage composite material.
6. The method for preparing the magnesium hydride-based hydrogen storage composite material according to claim 5, characterized in that: A hydrothermal reaction A is performed using a nickel source and a sulfur source to prepare NiS; Preferably, a molybdenum source and a sulfur source are used to carry out a hydrothermal reaction B to prepare MoS2. Preferably, the nickel source is a water-soluble salt of Ni ions, preferably at least one of nickel acetate, nickel nitrate, nickel sulfate, and nickel citrate; The sulfur source is sulfur and its compounds, preferably at least one of thiourea, sulfur, thioacetamide, sodium sulfide, and 1-butyl-3-methylimidazole thiocyanate; Preferably, the molybdenum source is a water-soluble molybdate, preferably at least one of sodium molybdate, ammonium molybdate, molybdenum oxide, and molybdenum; Preferably, in the hydrothermal reaction A, the molar ratio of Ni / S in the nickel source and the sulfur source is 1:(2-5); The temperature of hydrothermal reaction A is 200-240°C and the time is 18-30h; Preferably, in the hydrothermal reaction B, the molar ratio of Mo / S in the molybdenum source and the sulfur source is 1:(2-5); Preferably, the temperature of the hydrothermal reaction B is 200 to 240° C. and the time is 18 to 30 hours; Preferably, NiS and MoS2 are compounded based on ball milling, wherein the parameters of ball milling are: the ball-to-material ratio in the ball-to-material stage is (30-40):1, the ball milling speed is 300-500 rpm / min, the ball milling hydrogen pressure is 5-15 bar, and the ball milling time is 3-6 h.
7. The method for preparing the magnesium hydride-based hydrogen storage composite material according to claim 5, characterized in that: The raw material solution containing the nickel source, the sulfur source and the rGO is subjected to a hydrothermal reaction C treatment to obtain the NiS-rGO composite; Preferably, the temperature of the hydrothermal reaction C is 100-200° C. and the time is 18-30 hours.
8. The method for preparing the magnesium hydride-based hydrogen storage composite material according to any one of claims 5 to 8, characterized in that: The magnesium hydride and the modifier are compounded by ball milling, wherein the ball milling parameters are as follows: the ball-to-material ratio in the ball-to-material stage is (30-40):1, the ball milling speed is 300-500 rpm / min, the ball milling hydrogen pressure is 5-15 bar, and the ball milling time is 3-6 hours.
9. Use of the magnesium hydride-based hydrogen storage composite material according to any one of claims 1 to 4 or the magnesium hydride-based hydrogen storage composite material prepared by the preparation method according to any one of claims 5 to 8, characterized in that: It is used as a hydrogen storage active material.
10. A hydrogen storage device, characterized in that: The invention comprises the magnesium hydride-based hydrogen storage composite material as claimed in any one of claims 1 to 4 or the magnesium hydride-based hydrogen storage composite material prepared by the preparation method as claimed in any one of claims 5 to 8.
Citation Information
Patent Citations
Metal hydride compositions and lithium ion batteries
CN107004843A
A method for producing a metallic structure and a metallic structure obtainable by the method
CN110997189A
Bimetal sulfide composite magnesium-based hydrogen storage material and preparation method thereof
CN115159452A
A method for producing a metallic structure and a metallic structure obtainable by the method
EP3434391A1
Metal hydride compositions and lithium ion batteries
WO2016094493A1
